Capital Composition and the Declining Labor Share - Maya Eden; Paul Gaggl (Center for Economic Studies and ifo Institute (CESifo), 2019)
To what extent can technological advances in the production of capital account for the recent, worldwide decline in the labor income share? We pose two challenges to the automation narrative: first, estimates of the elasticity of substitution (EOS) between capital and labor tend to fall below or around one, suggesting that a decline in the price of capital should not lead to a decline in the labor income share. Second, we illustrate that, despite technological improvements, the price of capital relative to output has remained roughly constant, worldwide. This poses a challenge to the view that cheaper capital has caused the displacement of workers. We show that a more nuanced approach, which takes seriously the composition of capital, ascribes a prominent role to the automation hypothesis. Though information and communications (ICT) capital is a small fraction of the capital stock, it is highly substitutable with labor, and its user cost declined sharply over the last few decades. A framework that distinguishes between ICT and non-ICT capital is empirically plausible and suggests that automation accounts for more than one quarter of the global decline in the labor share, even if the aggregate EOS is substantially less than unity.
Keywords: E25; E22; J24; J31; O33; 330; technological change; labor share; ICT